A Nexus of CO2, Tourism Industry, GDP Growth, and Fossil Fuels - Shang, Yunfeng; Zhang, Ming; Chen, Mengya; Wang, Xueying; Dong, Yuting (Frontiers in Environmental Science, 2022)
The study especially investigated the nexus of CO2 emissions, tourism, fossil fuels and GDP growth using a data from 1970 to 2019 of China. The study applied the upset U-molded EKC using EKC and the ARDL models to calculate the time series stationarity variables. The results showed that in the initial phases of enlargement, sophisticated GDP adversely impacts CO2 emissions, then higher GDP positively influences CO2 emissions. The results reveal that the development in tourism, the use of coal and oil, and the growth of the population consume an important influence on CO2 emissions, whereas FDI besides population development had little effect. However, the usage of petroleum gas and electricity has little effect on CO2 emissions. As a matter of fact, these findings are important when it comes to devising measures to reduce the ecological damage caused by increased CO2 emissions. Withdrawing foreign direct investment, strengthening the use of sustainable electricity and improving transportation for explorers, especially the green tourism business are excellent ways to reduce environmental degradation in China.